CO2 emissions, economic growth and schooling. Subnational analysis for Ecuador - Massa Sánchez, Priscilla (2018)
In recent decades, CO2 emissions have grown steadily worldwide. In order to slow down or reduce environmental deterioration, it becomes difficult to argue that it can be achieved exclusively through the economic growth of the provinces. Moreover, unsustainable economic growth causes serious environmental damage. The estimates of the environmental Kuznets curve (CKA) show that environmental improvement does not depend solely on economic growth (VABPCSEMI); variables such as: the number of vehicles per capita (VEHICULOS), is a relevant variable that deserves to be taken into account in the design of public policies to reduce CO2 emissions (CO2PC), as well as the awareness and education (ESCOLARITY) of people that results in greater care and responsibility for the environment. In order to analyze these variables, information is taken from 21 provinces of Ecuador. The results show that the number of vehicles per capita expresses a direct relationship with CO2 emissions due to electricity consumption, since each vehicle on average generates 1.3 tons of CO2 per year. VAB per capita is significant and meets the theoretical expectation of a direct relationship between these two variables, stating that economic growth has an impact on CO2 emissions generated by electricity consumption.